Application of Vegetable Oil-Based Insulating Fluids for Transformers: A Review - Nguyen Van, Dung (VNU Journal of Science: Natural Sciences and Technology, 2019)
Vegetable oil-based insulating oils have been successfully applied in the field of insulation for distribution transformers because vegetable oils are fully biodegradable, high dielectric strength, high flash point and better compatible with paper insulators than mineral-based insulating oil. However, vegetable oils still have drawbacks such as high viscosity, high pour point, low oxidation stability and low resistance to the formation of fast mode streamers. Therefore, many studies have been performed to improve properties of vegetable oils. This paper will summarize the important research results on physicochemical properties of vegetable oils as well as the methods used to improve the efficiency of vegetable oils to establish a basis for determination of the research orientation in vegetable oil-based insulating oils in Vietnam.   Keywords: Vegetable oil, transformers, breakdown voltage, ageing, additives. References [1] Fotana, 50 years in the development of insulating liquids, IEEE Elec. Ins. Mag 29 (2013) 13-25. https://doi.org/10.1109/MEI.2013.6585853. [2] T.V. Oommen, Vegetable oils for liquid-filled transformer, IEEE Elec. Ins. Mag 18 (2002) 6-16. https://doi.org/10.1109/57.981322. [3] Y. Bertrand and L.C. Hoang, Vegetable Oils as Substitute for Mineral Oils, IEEE Proceeding of the 7th international Conference on Properties and Application Dielectric Materials, Nagoya, Japan, 2003. https://doi.org/10.1109/ICPADM. 2003.1218460. [4] D. Martin, Z.D. Wang, A.W. Darwin and I. James, A comparative study of the chemical stability of esters for use in large power transformers, Annual report of CEIDP, 2006. https://doi.org/10.1109/CEIDP.2006.311977. [5] C.P. McShane, J.L. Corkran, K.J. Rapp and J. Luksich, Natural ester dielectric fluid development, IEEE/PES Transmission & Distribution conference, USA, 2006. https://doi. org/10.1109/CEIDP.2006.311977. [6] M. Hrkac, P. Papageorgiou, I. Kosmoglou, G. Miatto, BIOTEMP® Transformer Technology for Innovative Compact Substation, 7th Mediterranean Conference and Exhibition on Power Generation, Transmission, Distribution and Energy Conversion, Agia Napa, Cyprus, 2010. https://doi.org/10.1049/cp.2010.0954. [7] Cooper, EnvirotempFR3 fluid formulated for performance, 2018. https://www.cargill.com/ doc/1432076501275/envirotemp-fr3-brochure.pdf (accessed 4 December 2019). [8] Working group A2.35, Technical brochure 436-Experiences in Service with New Insulating Liquids, Cigre, 2010. https://static.mimaterials. com/midel/documents/sales/New Experiences in Service with New Insulating Liquids.pdf (accessed 4 December 2019). [9] K. J. Rapp, J. Luksich and A. Sbravati, Application of natural ester insulating liquids in power transformers, Proceedings of My Transfo, 2014. https://smsystems.co.in/Natural Ester Power Transformers My Transfo 2014Final.pdf (accessed 4 December 2019). [10] R. Liao, J. Hao, G. Chen, Z. Ma, L. Yang, A comparative study of physicochemical, dielectric and thermal properties of pressboard insulation impregnated with natural ester and mineral oil, IEEE Trans. Dielectr. Electr. Insul 18 (2011) 1626-1637. https://doi.org/10.1109/TDEI.2011. 6032833. [11] S. Rahmat, Suwarno and S. Aminuddin, Effects of thermal ageing on the dielectric properties and dissolved gas analysis in ester from palm oil and kraft composite paper insulation, IEEE ICPERE, Indonesia, 2016. https://doi.org/10.1109/ICPE RE.2016.7904873. [12] M&I MATERIALS, MIDEL eN 1215, 2018. https://www.midel.com/app/uploads/2018/05/midel-en-1215-product-brochure.pdf (accessed 4 December 2019). [13] H.M. Wilhelm, M.B.C Stocco, L. Tulio, W. Uhren, S.G. Batista, Edible natural ester oils as potential insulating fluids, IEEE Trans. Dielectr. Electr. Insul 20 (2013) 1395-1401. https:// doi.org/10.1109/TDEI.2013.6571461. [14] Nguyen Van Dung, A study on breakdown properties of rice bran oil, Journal of Science and Technology-Da Nang University 7 (2016) 11-14. (in Vietnamese). http://tailieuso.udn.vn/handle/ TTHL_125/8625. [15] Nguyen Van Dung, A study on breakdown properties of corn oil and peanut oil, Journal of Science and Technology-Da Nang University 3 (2017) 34-37. (in Vietnamese). http://tailieuso. udn.vn/handle/TTHL_125/8241. [16] D.V. Nguyen, L.P. Nguyen, T.N. Quach, An investigation on breakdown properties of paper insulators impregnated with vegetable oils for transformers, IET Science, Measurement & Technology 13(2019), 1352-1361. https://doi. org/10.1049/iet-smt.2018.5580. [17] N.V. Dung, N.P. Long and L.Q. Khuong, Influence of vegetable oils on breakdown voltages of enamel insulation of transformer wire, IEEE GTSD 2018, Vietnam, 2018. https:// doi.org/10.1109/GTSD.2018.8595539. [18] A. Darwin, C. Perrier, P. Folliot, The use of natural ester fluids in transformers, Proceeding of Matpost 07, 2007. [19] S. Salaji, G. Ajithkumar, N. H. Jayadas, Pour point of vegetable oil based lubricants: effect of polymorphism, Technology letter 1 (2014) 23-37. [20] S. Asadauskas, S. Z. Erhan, Depression of pour points of vegetable oils by blending with diluents used for biodegradable lubricants, JAOCS 76 (1999) 313-316. https://doi.org/10.1007/s11746-999-0237-6. [21] Metrohm, Application bulletin 204/2e, Oxidation stability of oils and fats-Rancimat method. https://www.metrohm.com/en-vn/appli cations/AB-204 (accessed 4 December 2019). [22] S. Tenbohlen, and M. Koch, Ageing performance and moisture solubility of vegetable oils for power transformers, IEEE Trans. Power. Del 25 (2010) 825-830. https://doi.org/10.1109/ TPWRD.2009.2034747. [23] Nynas Nytro 10XN product data sheet. https:// www.nynas.com/en/product-areas/trans former-oils/oils/nytro-10xn/ (accessed 4 December 2019). [24] S.A. Ghani, N.A. Muhamad, Z.B.A. Noorden, H. Zainuddin, N.F. Ambo, Impact of using antioxidants on the breakdown voltage properties of natural ester insulation oil, International multi-disciplinary graduate conference of Terengganu, Malaysia, 2016. https://www.researchgate.net/publication/309732973 Impact of Using Antioxidants on the Breakdown Voltage Properties of Natural Ester Insulation Oil (accessed 4 December 2019). [25] EPA, 2002, Environmental technology verification report on BIOTEMP vegetable oil based insulating dielectric fluid. https://archive. epa.gov/research/nrmrl/archive-etv/web/pdf/06 vs abb.pdf (accessed 4 December 2019). [26] A. Beroual, U. Khaled, P.S. M. Noah, H. Sitorus, Comparatice study of breakdown voltage of mineral oil, synthetic and natural oils and based mineral oil mixtures under AC and DC voltages, Energies, 10 (2017) 1-17. https://doi.org/10.33 90/en10040511. [27] X. Wang, Z.D. Wang, Particle effect on breakdown voltage of mineral and ester based transformer oils, Annual report of CEIDP, Canada, 2008. https://doi.org/10.1109/CEIDP. 2008.4772859. [28] Q. Liu, Z. Wang, Streamer characteristic and breakdown in synthetic and natural ester transformer liquids under standard lightning impulse voltage, IEEE Trans. Dielectr. Electr. Insul 18 (2011) 285-294. https://doi.org/10.11 09/TDEI.2011.5704520. [29] L. Lewand, Doble engineeering, Understanding water in transformer systems, Neta World report, 2002. https://www.scribd.com/document/49912 551/Understanding-Water-in-Transformer-Systems (accessed 4 December 2019). [30] M.H.A. Hamid, M.T. Ishak, M.F.M. Din, N.S. Suhaimi, N.I.A. Katim, Dielectric properties of natural ester oils used for transformer application under temperature variation, Proceeding of PECon, Malaysia, 2016. https://doi.org/10.1109/ PECON.2016.7951472. [31] C. Perrier, A. Beroual, Experimental investigations on insulating liquids for power transformers: mineral, ester, and silicone oils, IEEE Elec. Ins. Mag 25 (2009) 6-13. https:// doi.org/10.1109/MEI.2009.5313705. [32] K. Bandara, C. Ekanayake, T. Saha, H. Ma, Performance of natural ester as a transformer oil in moisture-rich environments, Energies 9 (2016) 1-13. https://doi.org/10.3390/en9040258. [33] A. Munajad, C. Subroto, Suwarno, Study on the effect of thermal ageing on insulating paper for high voltage transformer composite with natural ester from palm oil using Fourier transform infrared spectroscopy (FTIR) and energy dispersive X-ray spectroscopy (EDS), Energies 10 (2017) 1-15. https://doi.org/10.3390/en 10111857. [34] A.P. McShane, K. J. Rapp, J. L. Corkran, G. A. Gauger, J. Luksich, Ageing of paper insulation in natural ester dielectric fluid, Proceeding of 2001 IEEE/PES Transmission and Distribution Conference and Exposition. Developing new perspectives, USA, 2001. https://doi.org/10.11 09/TDC.2001.971319. [35] J. Zhang, F. Wang, J. Li, H. Ran, X. Li, Q. Fu, Breakdown voltage and its influencing factors of thermally aged oil-impregnated paper at pulsating DC voltage, Energies 10 (2017) 1-16. https://doi.org/10.3390/en10091411. [36] CIGRE, Ageing of cellulose in mineral oil insulated transformers, CIGRE Brochure 323, 2007. https://www.academia.edu/37442177/323 AGEING OF CELLULOSE IN MINERAL-OIL INSULATED TRANSFORMERS (accessed 4 December 2019). [37] L.E. Lundgaard, W. Hansen, S. Ingebrigtsen, Ageing of mineral oil impregnated cellulose by acid catalysis, IEEE Trans. Dielectr. Electr. Insul 15 (2008) 540-546. https://doi.org/10.1109/ TDEI.2008.4483475. [38] L.E. Lundgaard, W. Hansen, S. Ingebrigtsen, D. Linhjell, M. Dahlund, Ageing of Kraft paper by acid catalyzed hydrolysis, IEEE ICDL, Portugal, 2005. https://doi.org/10.1109/ICDL.2005.1490105. [39] K.J. Rapp, C.P. McShane, J. Luksich, Interaction mechanisms of natural ester dielectric fluid and Kraft paper, IEEE ICDL, Portugal, 2005. https://doi.org/10.1109/ICDL.2005.1490108. [40] E. O. Aluyor, M.O. Jesu, The use of antioxidants in vegetable oils-A review, African Journal of Biotechnology 7 (2008) 4836-4842. https:// www.ajol.info/index.php/ajb/article/view/59677/47963 (accessed 4 December 2019). [41] A.A. Abdelmalik, Chemically modified palm kernel oil ester: a possible sustainable alternative insulating fluid, Sustain. Mater. Technol 1-2 (2014) 42-51. https://doi.org/10.1016/j.susmat. 2014.06.001. [42] T.V. Oommen, C.C. Claiborne, E.J. Walsh and J.P. Baker, A new vegetable oil based transformer fluid: development and verification, IEEE CEIDP, Canada, 2000. https://doi.org/10. 1109/CEIDP.2000.885288. [43] N. Beltrán, E. Palacios, G. Blass, Potential of Jatropha curcas oil as a dielectric fluid for power transformers, IEEE Electr. Insul. Mag 33 (2017) 8-15. https://doi.org/10.1109/MEI.2017.7866674. [44] V. Mentlik, P. Trnka, J. Hornak, P. Totzauer, Development of a biodegradable electro-insulating liquid and its subsequent modification by nanoparticles, Energies 11 (2018) 1-16. https://doi.org/10.3390/en11030508. [45] M. Karthik, M.W. Iruthayarajan and M. Bakrutheen, Investigation of vegetable oil blended with antioxidant, IEEE ICECCT, India, 2015. https://doi.org/10.1109/ICECCT.2015. 7225935. [46] A. Raymon, P.S. Pakianathan, M.P.E. Rajamani, R. Karthik, Enhancing the critical characteristics of natural esters with antioxidants for power transformer application, IEEE Trans. Dielectr. Electr. Insul 20 (2013) 899-912. https://doi.org/ 10.1109/TDEI.2013.6518959. [47] S.S. Kumar, M.W. Iruthayarajan, M. Bakrutheen, S.G. Kannan, Effect of antioxidants on critical properties of natural esters for liquid insulations, IEEE Trans. Dielectr. Electr. Insul 23 (2016) 2068-2078. https://doi.org/10.1109/TDEI.2016. 7556480. [48] A.A. Zaky, I.Y. Megahed, C. Evangelou, The effect of organic additives on the breakdown and gassing properties of mineral oils, J. Phys. D Appl. Phys 9 (1976) 841-849. https://doi.org/ 10.1088/0022-3727/9/5/017. [49] M. Unge, S. Singha, N.V. Dung, D. Linhjell, S. Ingebrigtsen, L. E. Lundgaard, Enhancements in the lightning impulse breakdown characteristics of natural ester dielectric liquids, Applied Physics Letters 102 (2013) 1-4. https://doi.org/ 10.1063/1.4803710. [50] L.A. Quinchia, M.A. Delgado, J.M. Franco, H.A. Spikes, C. Gallegos, Low-temperature flow behaviour of vegetable oil-based lubricants, Ind. Crops Prod 37 (2012) 383-388. https://doi.org/ 10.1016/j.indcrop.2011.12.021. [51] J. Li, Z. Zhang, P. Zou, S. Grzybowski, M. Zahn, Preparation of a vegetable oil-based nanofluid and investigation of its breakdown and dielectric properties, IEEE Electr. Insul. Mag 28 (2012) 43-50. https://doi.org/10.1109/MEI.2012.6268441. [52] M.S. Mohamad, H. Zainuddin, S.A. Ghani, I.S. Chairul, AC breakdown of natural ester mixed with iron oxide for oil-immersed power transformer application, IEEE SCOReD, Malaysia, 2015. https://doi.org/10.1109/SCOR ED.2015.7449315. [53] P. Zou, J. Li, C. X. Sun, Z. T. Zhang, R. J. Liao, Dielectric properties and electrodynamic process of natural ester-based insulating nanofluid, Mod. Phys. Lett. B 25 (2011) 2021-2031. https://doi. org/10.1142/S0217984911027285. [54] Y. Zhong, Y. Lv, C. Li, Y. Du, M. Chen, S. Zhang, Y. Zhou, L. Chen, Insulating properties and charge characteristics of natural ester fluid modified by TiO2 semiconductive nanoparticles, IEEE Trans. Dielectr. Electr. Insul 2 (2013) 135-140. https://doi.org/10.1109/TDEI.2013.6451351. [55] C. Tran Duy, O. Lesaint, A. Denat, N. Bonifaci, Streamer propagation and breakdown in natural ester at high voltage, IEEE TDEI 16 (2009) 1582-1593. https://doi.org/10.1109/TDEI.2009. 5361578. [56] J.C. Mendes et al., Advanced application of a natural ester vegetable oil in a HV power transformer, CIGRE, paper A2-101, 2008. https://library.e.abb.com/public/d9c7f1ba8834e4adc12577bb0037033c/Cigre%20Session%20Paper.pdf (accessed 4 December 2019). [57] Cooper power systems, B900-04062, E-FR3 large and medium power transformers users list (Retrofill & New installations), 2007. [58] Nguyen Van Dung, Nguyen Hoai Trung, A study on breakdown properties of coconut oil, Vietnam Journal of Science and Technology 57 (2019) 320-328. https://doi.org/10.15625/2525-2518/57 /3/13212.